Cardiac radioablation for ventricular tachycardia: Which approach for incorporating cardiorespiratory motions into the planning target volume?. (March 2022) - Bellec, Julien; Rigal, Louis; Hervouin, Aurélien; Martins, Raphaël; Lederlin, Mathieu; Jaksic, Nicolas; Castelli, Joël; Benali, Karim; de Crevoisier, Renaud; Simon, Antoine
Highlights: Cardiorespiratory ITV generated using cardiac-gated and respiratory-gated 4DCT. Cardiorespiratory motions lead to an important increase of target volume in cardiac radioablation. Combining 2 cardiac phases with 10 respiratory phases is a robust approach. Using a single cardiac phase with our without fixed margin is a suboptimal approach. Abstract: Purpose: To evaluate different approaches for generating a cardiorespiratory ITV for cardiac radioablation. Methods: Four patients with ventricular tachycardia were included in this study. For each patient, cardiac-gated and respiration-correlated 4D-CT scans were acquired. The cardiorespiratory ITV was defined using registrations of the cardiac and respiratory 4D-CT images. Five different approaches, which differed in the number of incorporated cardiac phases (1, 2, 10, or 1 with a fixed 3 mm margin (FM) expansion) and respiratory phases (2 or 10), were evaluated. For each approach, a VMAT treatment plan was simulated. Target coverage (TC) and spill were evaluated geometrically and dosimetrically for each approach. Results: When employing one cardiac phase, the TC did not exceed 85%. Using the two extreme phases of the cardiac and respiratory cycles resulted in a geometric TC < 88% for two patients, with a dosimetric TC of 83% for one patient. An acceptable TC for all patients (geometric TC > 89%, dosimetric TC > 92%) was only achieved when combining 10 respiratory phases with either 2 or 10 cardiac phases or a single cardiac phase with FM. The use of a single cardiac phase with FM combined with 10 respiratory phases lead to a mean geometric and dosimetric spill of 43% and 35%, respectively. Conclusion: For cardiac radioablation, the use of two extreme cardiac phases combined with 10 respiratory phases is a robust approach to generate a cardiorespiratory ITV. The use of a single cardiac phase with or without fixed margin expansion is not recommended based on this study.